Effect of aromatase inhibitors on ectopic endometrial growth and peritoneal environment in a mouse model of endometriosis - Bilotas, Mariela Andrea (2010)
Objective: To evaluate the effect of aromatase inhibitors on ectopic endometrial growth and on the release of proangiogenic and proinflammatory factors in peritoneal fluid (PF). Design: Prospective experimental study. Setting: Animal research and laboratory facility. Animal(s): Female Balb/c mice 2 months of age. Intervention(s): Mice had surgery performed to induce endometriosis-like lesions. Treatment with anastrozole or letrozole was started on either postoperative day 1 or 28 and continued for 4 weeks. Main Outcome Measure(s): Endometriotic lesions were counted and measured and aromatase expression, cell proliferation, and apoptosis were assessed. Vascular endothelial growth factor (VEGF) and prostaglandin E (PGE) levels were evaluated in the PF. Result(s): Endometriosis-like lesions express aromatase P-450. Treatment with either anastrozole or letrozole did not prevent lesion establishment; however, it significantly decreased the size of the endometriotic lesion. When treatment was initiated on postoperative day 1, letrozole and anastrozole decreased cell proliferation and increased apoptosis. When treatment was started on postoperative day 28, both aromatase inhibitors decreased cell proliferation, but only anastrozole augmented apoptosis levels. In addition, letrozole reduced VEGF and PGE levels in PF. Anastrozole diminished VEGF content but did not cause any significant change in PGE levels. Conclusion(s): These findings support the further investigation of aromatase inhibition as a treatment option for endometriosis. © 2010 American Society for Reproductive Medicine.